Analysis of heat transfer characteristics in textiles and factors affecting thermal properties by modeling. Issue 21 (November 2019) - Shen, Hua; Xie, Kaifang; Shi, Haoxuan; Yan, Xiaofei; Tu, Lexi; Xu, Yanfang; Wang, Jilong
The heat transmission through a fabric during the measurement of thermal resistance was simulated by a novel heterogeneous model that was constructed according to the structure of ThermolabII Tester KES-F7. In this model, the heat transmissions along the longitudinal and transverse directions of yarn were treated independently. The material constants of fabrics, such as mass density, specific heat, thermal conductivity and thickness, were used as parameters for simulation in this fabric model. The validity of this model was then confirmed by the high consistency between the heat flux obtained from experiment and simulation, with the average difference ratio lower than 5%. The simulation results suggested that the guard area could effectively reduce the horizontal heat leakage from the test plate when the experimental fabric was thin. Only less than 8% of heat leaked in the one-layer case, while the leakage was significantly aggravated when more layers of fabric were stacked, resulting in the considerably lower thermal insulation achieved in both experiment and simulation compared with that in real fabrics. The temperature distribution in the model also implied that the longitudinal and transverse thermal conductivity of yarn exerted great effect on the heat leakage during the measurement. Moreover, for multilayers consisting of different fabrics, the laying sequence could obviously influence the heat leakage and, consequently, change the obtained thermal resistance.